Using Targeted Virotherapy to Treat a Resistant Ewing Sarcoma Model: From the Bedside to the Bench and Back - Hesham Abdelbary; Christopher W. Brown; Joel Werier; John Bell (The Scientific World Journal)
Metastatic Ewing sarcoma (EWS) is often resistant to current multimodal chemotherapeutic regimens. Oncolytic virus therapy (OV) is a novel therapeutic platform whereby viruses can selectively infect as well as replicate in and kill tumor cells, while sparing normal tissues. The purpose of this study is to investigate the efficacy of the biotherapeutic oncolytic agent, vesicular stomatitis virus (VSVΔM51), to kill EWS cells that are resistant to conventional therapy. Our hypothesis is that systemic delivery of VSVΔM51 can demonstrate tumor-specific killing of resistant EWS cells, as well as a significant decrease of tumor burden in EWS bearing mice. Methods. A biopsy sample was obtained from a patient with metastatic EWS and was used to establish a novel EWS cell line. In vitro assays evaluated the oncolytic effect of vesicular stomatitis virus (VSVΔM51) on this cell line. EWS xenograft mice model bearing either lung or subcutaneous tumors was established to evaluate the antitumor specific oncolytic effect of VSVΔM51 after local and systemic delivery. Results. The established EWS cell line shared similar molecular and genetic traits to the patient’s original tumor specimen. VSVΔM51 effectively infected and killed EWS cells in vitro. In vivo, VSVΔM51 selectively infected and killed EWS and led to significant delay in tumor growth. Conclusion. This study has been designed to implement a translational link between the bedside and the bench, where a specific challenging clinical scenario guided this basic science research. This research demonstrated that a sarcoma, which is resistant to current conventional standard therapies, is still susceptible to an alternative therapeutic platform, such as OV. Adding OV to the armamentarium of sarcoma treatment can enhance the future therapeutic approach towards these cancer patients.